Understanding the impact of ER stress on lung physiology - Fu, Zhiling; Wang, Wei; Gao, Yuan (Frontiers in Cell and Developmental Biology, 2024)
Human lungs consist of a distinctive array of cell types, which are subjected to persistent challenges from chemical, mechanical, biological, immunological, and xenobiotic stress throughout life. The disruption of endoplasmic reticulum (ER) homeostatic function, triggered by various factors, can induce ER stress. To overcome the elevated ER stress, an adaptive mechanism known as the unfolded protein response (UPR) is activated in cells. However, persistent ER stress and maladaptive UPR can lead to defects in proteostasis at the cellular level and are typical features of the lung aging. The aging lung and associated lung diseases exhibit signs of ER stress-related disruption in cellular homeostasis. Dysfunction resulting from ER stress and maladaptive UPR can compromise various cellular and molecular processes associated with aging. Hence, comprehending the mechanisms of ER stress and UPR components implicated in aging and associated lung diseases could enable to develop appropriate therapeutic strategies for the vulnerable population.